Nowe zasady dokonywania podziałów województw na obwody łowieckie - Zacharczuk, Piotr (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Due to the recent normative legislation amendments, the issue of voivodeships division into hunting zones is extremely topical. As part of these normative amendments, the legislature have implemented the judgment of the Constitutional Tribunal of 10 July 2014 (reference number P 19/13). However, it has taken over 3 years and 8 months until the legislature have implemented the judgment of the Constitutional Tribunal. The relevant statutory laws came into force only on 1 April 2018.Unfortunately, amendments complied and adopted to the act of Hunting Law turned out to be only fragmentary.. The legislature, contrary to the suggestions of the Constitutional Tribunal, have not compiled completely new comprehensive statutory law. Within the act of 22 March 2018 amending the act on Hunting Law and certain other acts, the legislature, in particular, specified exhaustively the content of the resolutions on the voivodeships division into hunting zones, as well as the qualification of hunting zones into particular categories, and also significantly developed the procedure of these resolutions compiling and adopting, by, for example, means of devolution of powers within the procedure. Nevertheless, these normative amendments are not free from legislative shortcomings. No resolution has yet been adopted to this new legal basis. The reason for the lack of greater activities of the competent authorities within this area is mainly that the deadline for adopting of the first resolutions on the voivodeships division into hunting zones, as well as hunting zones qualification into particular categories, is on March 31, 2020.